INVENTARISASI DAN IDENTIFIKASI TAMBANG DI KABUPATEN MURUNG RAYA DAS BARITO HULU - Karta Sirang (Jurnal Hutan Tropis, 2011)
Act No. 41 of 1999 mandates that the forest can be utilized for other sectors outside the forestry sector in accordance with the regulations and provisions of the rights and obligations are binding on each of the use or utilization. Forestry ministry to allow use of forest area borrowed Minister of Forestry: Guidelines for Borrow Wear P.43/Menhut-II/2008 Forest, including for the activity of mining Activities Inventory and Identification of Areas Mining in forest areas in Hulu Barito river basin is to determine the use of forest areas outside the forestry sector, particularly for the mining sector. The results obtained that the Inventory and Identification; Potential types of mining and quarrying in the district Murung Kingdom is Coal, Gold, Diamond, Lime, Bentonite, Stone and Sand, The form of licensing status Feasibility Study 2 companies, licensing status Form of Construction 2 companies and licensing status PKB2B form of Constantine and 27 Exploration and Mining Company perysahaan have fare SK Borrow Wear Forest Zone 6 companies.